Long-term follow-up of kidney transplant recipients with polycystic kidney disease - Mehrabi, Arianeb; Golriz, Mohammad; Maier, Julia; Fonouni, Hamidreza; Garoussi, Camelia; Hafezi, Mohammadreza; Fard-Rutherford, Nassim; Faridar, Alireza; Rezaei, Nahid; Wiesel, Manfred; Mieth, Markus; Morath, Christian; et al. (Experimental and clinical transplantation, 2015)
OBJECTIVES: Patients with polycystic kidney disease are candidates for kidney transplant. We report the results of our single center study of 250 first transplant recipients with polycystic kidney disease (autosomal dominant [64%], medullary cystic [16%], autosomal recessive [6%], and nonspecified [14%]). - MATERIALS AND METHODS: Patient groups were divided and analyzed according to the origin of the graft (deceased donor or living donor). We also analyzed demographic data of donors and recipients, waiting time, duration of dialysis, transfusion, nephrectomy, hospitalization, morbidities, and graft and patient survival. The study was approved by the Ethical Review Committee of the Institute. All of the protocols conformed to the ethical guidelines of the 1975 Helsinki Declaration. - RESULTS: The deceased-donor group comprised 79% and the living-donor group comprised 21% of the cases. Nephrectomy was performed on 21% of the recipients. The deceased-donor group showed significantly higher values than the living-donor group regarding rate of hemodialysis (82% vs 68%), duration of dialysis (1571 vs 1002 days), waiting time (1129 vs 33 days), and blood transfusions (45% vs 27%). In deceased-donor versus living-donor transplant recipients, surgical complications included arterial stenosis (1% vs 0%), venous thrombosis (1% vs 0%), urine leakage (0.5% vs 1.9%), ureteral stenosis (0.5% vs 0%), reflux (0% vs 1.9%), lymphocele (11.7% vs 8.1%), and hernia (5.2% vs 8.1%), with no statistically significant differences shown between the groups. The living-donor group had graft and patient survival rates as high as the deceased-donor group. - CONCLUSIONS: The low rate of morbidity and excellent survival rates make kidney transplant an excellent option for patients with polycystic kidney disease. Although fear of future appearance of polycystic kidney disease may reduce the rate of related living donors, our study showed that graft and patient survival rates in the living-donor group were as high as in the deceased-donor group.